Why isn’t urban development sustainable? An institutional approach to the case of Athens, Greece - Antonios Tsiligiannis (Journal of Contemporary Urban Affairs, 2020)
Despite the rise to prominence of sustainable planning, the state of urgency and the pressure imposed by the extreme competition between metropolitan territories reduce sustainability to a market-oriented doctrine for deregulated urban development. The aim of this article is an exploration of the current Athenian urban crisis, by centring on sustainable urban development plans, territorial planning institutions, and urban policies. To this end, the phenomenon of urban crisis is explained as a derivative of the failure of sustainability reforms. By establishing a link between the institutional framework governing urban development and the success or failure of sustainability reforms, this article seeks to contribute to the discussion around the attainability, scope and impact of sustainable urban development plans. Through the hypothesis that as long as territorial planning is used as means towards speculative urban development, it will only be equivalent to that of a real estate facilitating mechanism, it is argued that the urban development model of Athens, as well as the role that institutions have in its shaping, is incompatible with any notion of sustainability. The main contribution of this article is to potentially help towards developing a critical reflection on how projects, plans, territories and sustainability should be approached.